For the love of lists: identifying the effects of listicle type and length. Issue 4 (2nd October 2021) - Freeman, Jason; Buckley, Christen; Triptow, Christina; Chai, Yiting
ABSTRACT: Entire journalistic empires have been built upon sensational headlines designed to elicit consumer attention and provide advertising partners with what they want most: eyeballs on content. Listicles are used widely for that purpose with little research addressing effective design and viewer perceptions of use. This study proposes the following questions: what are the psychological mechanisms behind a user's experience with various listicle forms? How does the clickability and length of a listicle influence consumer responses? To answer these questions, a 2 × 2 between-subject experiment was conducted. Findings demonstrated that clickable listicles (vs. scrollable) provide users with greater control, which in turn positively predicted a variety of cognitive outcomes and emotional and attitudinal communicative outcomes. In addition, longer listicles led to greater frustration, which in turn negatively impacted these outcomes. Theoretical and practical implications are discussed.